Magnetic flux signal extraction method based on wavelet threshold filtering. Issue 3 (February 2019) - Huang, Kui; Dai, Jialong; Xu, Chaoqun; Yi, Zhong; Meng, Lifei
Abstract: Magnetic detection based on magnetic flux induction coil is an important means of moving target detection and tracking, which can be applied to various complex environments. Among them, the extraction of the magnetic flux signal of the moving target under complex background conditions is a key technology. This paper first introduces the basic principle of the magnetic flux detection method. According to the different characteristics of the target magnetic flux signal and the noise signal, comprehensively considering the characteristics and applicable range of various signal filtering and noise reduction methods, the wavelet threshold denoising method is selected to carry out the signal. In the laboratory environment, a magnetic flux detection method test system for moving targets was built. The signal extraction method was used to analyse and process the test data and compared with the simulation results. The results show that the filtering method can effectively filter out the Gaussian white noise in the flux signal, separate the signals of different frequencies, and retain the characteristics of the target signal, thus verifying the feasibility and applicability of the method.